An Optimized Synergetic Nonlinear Controller (OSNC) based maximum power point tracking for a standalone photovoltaic system using a boost converter - Awe Taissala; Deli Goron; Nicodem Nisso; Dieudonné Kaoga Kidmo; Paul-Salomon Ngohe Ekam; Fabrice Kwefeu Mbakop; Noël Djongyang (Energy Reports, 2022)
In this paper, an Optimized Synergetic Nonlinear Controller (OSNC) is proposed to efficiently determine the maximum power point of a Photovoltaic Generator matched to the load through a DC–DC boost converter. The dynamic equation of the conventional synergetic controller is modified to adjust the Manifold in such a way that the optimum maximum power point (MPP) is reached. This new approach is implemented in the Matlab/Simulink software and shows increased convergence in steady and transient states. Consequently, this new approach exhibits better performance than the conventional nonlinear synergetic controller (SNC) in standard test conditions and weather varying conditions.